(untitled) (The Peerian Journal, 2026)
This study is devoted to evaluating the dynamics of complex treatment of acute odontogenic osteomyelitis of the mandible in children using thermovisiography. Acute odontogenic osteomyelitis is one of the severe purulent-inflammatory diseases of the maxillofacial region in children, which, if not diagnosed and treated in a timely manner, can lead to bone tissue necrosis, sequestration, and severe functional impairments. The study included 30 children diagnosed with acute odontogenic osteomyelitis of the mandible. Patients were divided into two groups: a control group (15 patients) and a main group (15 patients). In addition to standard treatment (antibacterial, detoxification, symptomatic therapy, surgical intervention), patients in the main group received low-level laser therapy. Treatment dynamics were assessed using thermovisiography. The results showed that in the main group, thermal asymmetry in the inflammatory focus decreased faster (significant difference on days 3-5, p